Eugen Barbu: debut editorial surprinzător şi controversat (1955–1960) - Pavel Ţugui (Revista de Istorie și Teorie Literară)
The article aims at presenting a detailed picture of the Romanian literary life of the (mid to late) ’50s and correcting particular details concerning the debut of Eugen Barbu (1924–1993), Romanian journalist and prose writer, a disputed literary figure of the Communist era. The author puts forward some critical remarks on Mihai Ungheanu’s work of editing the texts of Eugen Barbu, drawing attention upon the errors this editor has done, purposely or unknowingly. He offers further information about the context in which the novel Groapa (The Pit) was published and new data on the project of another novel written by Eugen Barbu, Calea Negustorilor (The Traders’ Route). The author of the article, as a direct participant in the literary and cultural life of that time, gives the perspective of an insider when he relates the events connected with the life and work of this novelist. The article is rich in critical commentaries and new biographical information about Eugen Barbu.